Significance of secondary forces toward improving the charge carrier mobility of Isoindigo based conjugated small molecules - Dharmapurikar, Satej S.; Kashmir, Arulraj Arul; Kumari, Tanya; Kalalawe, Virbhadra; Kanetkar, Maruti; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2021)
The charge carrier mobility of conjugated small molecules (CSMs) depends on the intermolecular interactions and morphology. Herein, we report the synthesis of CSMs having different side chains. Hydrogen bonding, lipophilic imbalance and van der Waals interactions are imparted through the asymmetric substitution of Isoindigo. The secondary forces impact thin film morphology, and charge carrier mobility. The CSMs having van der Waals interaction further shows higher charge carrier mobility as a function of improved morphology, and increased temperature. The highest mobility of 0.15 cm2/Vs has been achieved for CSMs with van der Waals interaction.
Keywords: Conjugated small molecules; Isoindigo; mobility; OFET; Secondary force